Meditations on a Monkey-Face: Monsters, Transgressed Boundaries, and Contested Hierarchies in a Yiddish Eulenspiegel - Idelson-Shein, Iris (The Jewish quarterly review, 2018)
This paper discusses an early-eighteenth-century Yiddish translation of the famous early modern Schwankroman (jest-novel), Eulenspiegel. The uniqueness of the translation lies in its incorporation of five distinct tales, which do not appear in any other extant Jewish or non-Jewish edition. Four of these original tales feature monstrous creatures, such as cynocephali (dog-headed men), strong, venomous women, and monkey-faced men. The article offers a close reading of these monstrous creatures, revealing how they serve to unpack concerns surrounding problems of transgressed borders and confused hierarchies, which were shared by many of the unnamed Yiddish translator's Jewish and non-Jewish contemporaries. I offer a review of these anxieties, locating them against their wider cultural background, and tracing their unique manifestations within the Jewish—and particularly Yiddish—literary realm. I argue that there was something special about writing monstrosity in Yiddish, and particularly in a Yiddish translation of a German work. A hybrid genre, formed by the unnatural coupling of separate tongues, literature, cultures, classes, and genders—Yiddish literature was a monstrous creation in its own right; an almost natural breeding ground for monsters.